MicroRNAs in platelet production and activation. (30th June 2013) - Edelstein, L. C.; McKenzie, S. E.; Shaw, C.; Holinstat, M. A.; Kunapuli, S. P.; Bray, P. F.
Summary: Recent work by the Encyclopedia of DNA Elements project showed that non‐protein‐coding RNAs account for an unexpectedly large proportion of the human genome. Among these non‐coding RNAs are microRNAs (miRNAs), which are small RNA molecules that modulate protein expression by degrading mRNA or repressing mRNA translation. MiRNAs have been shown to play important roles in hematopoiesis including embryonic stem cell differentiation, erythropoiesis, granulocytopoiesis/monocytopoiesis, lymphopoiesis, and megakaryocytopoiesis. Additionally, disordered miRNA biogenesis and quantitative or qualitative alterations in miRNAs and their targets are associated with hematological pathologies. Platelets contain machinery to process pre‐miRNAs into mature miRNAs, and specific platelet miRNA levels have been found to correlate with platelet reactivity. This review summarizes the current state of knowledge of miRNAs in megakaryocytes and platelets, and the exciting possibilities for future megakaryocyte–platelet transcriptome research.